HUBUNGAN ANEMIA DENGAN TINGKAT KEPARAHAN DAN PERJALANAN PENYAKIT STROKE ISKEMIK AKUT - Eugenia Isadora; Budi Riyanto Wreksoatmodjo; Tara Puspitarini Sani (PERDOSNI, 2021)
Introduction: Stroke is the second leading cause of death and the third leading cause of disability throughout theworld. Anemia or reduced hemoglobin level can worsen the tissue damage caused by ischemia; including ischemic braintissue caused by ischemic stroke. Aim: This research aims to determine the association between anemia and stroke severity and clinical course basedon the NIHSS score among acute ischemic stroke patients in Atma Jaya Hospital during 2014-2019 Methods: A cross-sectional study using secondary data from Atma Jaya Stroke Registry from 2014-2019. A totalsampling method obtained 347 samples with complete pertinent data. Anemia was defined as Hb level <12 g/dL for womenand <13 g/dL for men. Stroke severity was measured by NIHSS score. Association between variables was calculated withthe chi-square test. Results: The risk factor associated with the severity of stroke was hypertension (p=0.013). There was no significantassociation between anemia and stroke severity on admission (p=0.895) and hospital discharge (p=0.773). There was nosignificant association between anemia and the clinical course of acute ischemic stroke (p=0.09). Discussion: Factors that may contribute to the various results of similar studies were differences in study design,anemia as a comorbid condition, genetic factors, sample size, and differences in measurement methods of stroke outcomeor severity. Keywords: Anemia, ischemic stroke, NIHSS, severity